2020
DOI: 10.1007/s10608-020-10163-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-Regulation in Psychosis: Patients with Psychotic Disorders Apply Reappraisal Successfully

Abstract: Background Emotion-regulation is assumed to be impaired in psychosis: patients with psychotic disorders (PD) self-report to use reappraisal less frequently than healthy controls (HC), but it is uncertain whether they are also less successful in applying reappraisal. Moreover, it has not been investigated whether the habitual use of reappraisal is associated with the ability to use reappraisal successfully. Methods To address these questions, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…It is worth noting that the levels found in alexithymia in our research were higher than in the normal population; similarly, the subject’s enjoyment of life was lower than in the population, but relatively similar to the clinical sample in a previous study [ 29 ]. It is inferred that students with psychosis will obtain high levels of alexithymia in line with previous studies [ 15 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is worth noting that the levels found in alexithymia in our research were higher than in the normal population; similarly, the subject’s enjoyment of life was lower than in the population, but relatively similar to the clinical sample in a previous study [ 29 ]. It is inferred that students with psychosis will obtain high levels of alexithymia in line with previous studies [ 15 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…The test reached a Cronbach's alpha consistency index of 0.078 [28]. -Savoring Beliefs Inventory (SBI), Spanish version of [29] of the original scale of [30] It consists of 24 items expressed by means of a Likert-type scale that goes from 0 = Nothing to 4 = A lot or Extremely, distributed in three factors: "Anticipation" refers to the ability to be able to visualize a pleasant event or situation before it happens and is composed of items 1, 4, 7, 9, 10, and 13 (e.g., "I don't like to think in advance about good times before they happen"); "Enjoy a present moment" is the capacity to be able to find pleasure in carrying out an activity at present and is composed of items 2, 3,5,11,15,17,18,19,21, and 23 (e.g., "I enjoy remembering the happy moments I have experienced in my past"); and "Reminiscence" which is the ability to be able to evoke a positive event that has happened before, being composed of items 6, 8, 10, 12, 14, 16, 20, 22, and 24 (e.g., "When it comes to enjoyment I am "my worst enemy"). The overall internal consistency measured through Cronbach's alpha was 0.91.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of questionnaire studies examining the frequency of strategies showed that individuals with psychosis typically report to use more dysfunctional and less functional strategies than healthy controls (Ludwig et al, 2019b). In contrast to the consistent picture presented by these studies, experimental studies that commonly induce affect along with the instruction to use a certain emotion regulation strategy tend to find that individuals with psychosis are as successful as healthy controls in effectively down-regulating their negative affect (Grezellschak et al, 2015;Opoka et al, 2020Opoka et al, , 2021Perry et al, 2012;Van Meer et al, 2014). Putative reasons for the discrepancy between the findings in questionnaire and experimental studies are a retrospective recall bias in the questionnaire studies and the artificialness of the instructions in the experimental design and the induced emotion, which questions their ecological validity.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with psychosis may use thought suppression as a cognitive coping strategy (e.g., to reduce the distress associated with the delusions and/or auditory hallucinations); however, as stated earlier, with a potential rebound effect [ 21 ]. There is evidence that psychotic patients also use cognitive reappraisal frequently to reduce negative emotions, such as anxiety or depression [ 22 ]. However, research indicates that there is a preference for suppression over cognitive reappraisal among psychotic patients who experience positive symptoms [ 23 ].…”
Section: Introductionmentioning
confidence: 99%